Prevalence and predictors of long corrected QT interval in HIV-positive patients: a multicenter study. Issue 7 (July 2017) - Gili, Sebastiano; Mancone, Massimo; Ballocca, Flavia; Grosso Marra, Walter; Calcagno, Andrea; D'Ettorre, Gabriella; Cannillo, Margherita; D'Ascenzo, Fabrizio; Orofino, Giancarlo; Marruncheddu, Laura; Lonni, Enrica; Cinque, Alessandra; et al.
Abstract : Aims: HIV and highly active antiretroviral therapy (HAART) may affect cardiac conduction, and a higher incidence of sudden death has been recognized in HIV-positive patients. Nevertheless, predictors of prolonged corrected QT interval (cQT) have been poorly described. The aim of the study was to investigate the prevalence and predictors of long cQT in a cohort of HIV-positive patients. Methods: Consecutive HIV-positive patients followed in a primary prevention clinic at two Italian institutions were retrospectively enrolled. A 12-lead ECG was recorded in all patients; main clinical features were collected. Prevalence of long cQT (defined as cQT >470 ms in women and >450 ms in men) was the primary end-point. Secondary end-points were the identification of predictors of cQT prolongation, and the association between HAART and HIV-related features with long cQT. Results: Three hundred and fifty-one HIV-positive patients were included, 26 (7.4%) with long cQT. Mean age was higher among those with long cQT (51.6 vs. 57.6 years; P  = 0.007). A higher prevalence of long cQT was reported for patients with a CD4+ cell count below 200 cells/μl at the moment of ECG (60 vs. 24.2%; P  = 0.002) and with a nadir of CD4+ cell count below 200 cells/μl (91.3 vs. 58.6%; P  = 0.001). At multivariate analysis, only the nadir of CD4+ cell count below 200 cells/μl consistently related to the presence of long cQT (odds ratio 5.8, 95% confidence interval 1.3–26.4). Conclusion: A low CD4+ cell count is associated with long cQT independently from HAART in HIV-positive patients and may be useful to correctly stratify arrhythmic risk in these patients.